Pengkondisian Gelombang Otak Zona Alfa Melalui Apersepsi Pembelajaran - Ulfa Ainul Mardhiyah (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
In the learning process, the communication that should be built in not one- way communication, but two-way communication where students are able to send and receive messages. There is feed back from the recipient of the messageswhich is also used by the sender of the message as an indication of the effectiveness of the messages that has been previously conveyed, the brain’s work sequence of reactions is very closely related to one another, there is to one another, there is one brain wove, which is based an research, which is one of the right conditions to star the learning process namely the alph zona brain waves, there for it is needed a special stimulus to memorize the student’s brain. So that student’s can focus, concentration so that the reptile brain of the student is brain of the student is satisfied and ready to lern. The quality of the apperception of learning carried out by the teacher of ten runs less optimaly to be able to bring student’s to the alpha zone, it is necessarry to have a technique that is able to increase the work of the brain so that it reaches the alpha zone condition, somes teps that can be applied in apperception include fun story, music, braingym, warmer, scense setting.